Analysis of Factors Influencing Muslim Consumer Decisions in Purchasing Halal Products - Muhammad Rifki; Fathur Rozi; Diana Putri Anggraini (Penerbit Hellow Pustaka, 2025)
This study aims to analyze in depth the factors that influence the decision of Muslim consumers to buy halal products in Indonesia. Using a descriptive qualitative approach, this study explores consumer perceptions, experiences, and considerations through literature, books, interviews, observations, and documentation. The results of the study show that the decision to purchase halal products is influenced by a number of factors that interact with each other, including religiosity, halal literacy, trust in halal certification, risk perception of non-halal products, and product quality and value. Social factors such as family, religious communities, and religious leaders also shape preferences and increase consumer awareness of the importance of consuming products in accordance with sharia. The research also found that government regulations through the Halal Product Assurance Law (JPH Law) strengthen public trust and encourage producers to be more transparent in the production process. Halal logos are an important indicator in consumer evaluation, while price factors, brand image, and marketing strategies that highlight Islamic values also influence purchasing decisions. In addition, digital media plays a big role in expanding halal literacy and shaping consumer opinion. Overall, the decision to purchase halal products is the result of a combination of religious motivation, knowledge, quality perception, social influence, and government policies. These findings provide implications for manufacturers, marketers, and regulators in developing more effective marketing and oversight strategies in the halal industry.